Automation in Traffic Engineering to Prevent Road Accidents: A Review - Musarat, M.A. (Institute of Electrical and Electronics Engineers Inc., 2021)
Road accidents are one of the leading fatality rates around the globe. Even with advancements in technologies, still, the reduction in accidents is minimal. This review intends to evaluate the studies on automated prevention for road accidents. In this manner, the PRISMA statement was executed, and data extraction was made from the Scopus database. By initial screening, 75 articles were extracted, while performing the detailed screening only 22 left for final assessment. The keywords combinations were 'Automation' AND 'Road Accidents' with year limitation from 2011 to mid-2021. The extracted articles were focusing on automation aiding drivers, automation in automated vehicles, automation in crash reduction and automation aiding pedestrians, cyclists and mixed vehicles. The adaptation of these automation techniques in road safety can reduce the fatality rate, especially in developing countries where the rate is high and requires a major transformation in infrastructure. Â© 2021 IEEE.